Femtosecond pulse generation by actively modelocked fibre ring laser. Issue 8 (1st April 2013) - Nguyen, D.T.; Muramatsu, A.; Morimoto, A.
Abstract : Femtosecond optical pulses are generated by an actively modelocked fibre ring laser. The fibre ring cavity includes a dual‐electrode Mach‐Zehnder optical intensity modulator and an erbium‐doped fibre amplifier. To generate femtosecond pulses, fast impulse modulation is employed. The modelocking generates femtosecond pulses with a pulse‐width of about 500 fs.